MANAJEMEN PENGUATAN KARAKTER PESERTA DIDIK DI MADRASAH TSANAWIYAH PONDOK PESANTREN MODERN TARBIYAH TAKALAR - Aspirah, Aspirah; Yuspiani, Yuspiani; Awaliah Musgamy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the management of strengthening students’ character at Madrasah Tsanawiyah of Pondok Pesantren Modern Tarbiyah Takalar. The study aims to analyze management planning and character-strengthening programs, the factors influencing their success, and the impacts of their implementation. This research employs a qualitative approach with a descriptive study design. Data were collected through interviews, observations, and documentation, with data sources including the principal, vice principal, teachers, and dormitory supervisors. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results show that character-strengthening management planning is implemented in a structured, systematic, and sustainable manner by involving all school stakeholders and is realized through three flagship programs, namely Tahfiz, Language, and Dai-daiyah. Program implementation is carried out through daily, weekly, monthly, and annual activities, such as Qur’an memorization, language practice and tests, competitions, and da’wah activities, which aim to instill the values of discipline, responsibility, religiosity, self-confidence, leadership, politeness, and noble character. The success of the programs is influenced by the exemplary behavior of teachers and mentors, consistency in habituation methods, comprehensive supervision, and the dormitory environment as the main medium for character formation. The character-strengthening programs have a positive impact on students’ attitudes and behavior, as indicated by improvements in discipline, responsibility, ethics, obedience in worship, emotional control, and cooperation. In the long term, these programs are expected to produce students with integrity, independence, and strong moral foundations. These findings indicate that pesantren-based character-strengthening management can serve as an effective alternative model for building students’ character in a sustainable manner.